Phospholipase C?1 is required for metastasis development and progression - Sala, G.; Dituri, F.; Raimondi, C.; Previdi, S.; Maffucci, T.; Mazzoletti, M.; Rossi, C.; Iezzi, M.; Lattanzio, R.; Piantelli, M.; Iacobelli, S.; Broggini, M.; et al. (American association for Cancer Research, 2008)
Cell motility and invasion play an essential role in the development of metastasis. Evidence suggests that the enzyme phospholipase C?1 (PLC?1) may be involved in tumor progression and possibly development of metastasis. In this study, we show that down-regulation of PLC?1 expression severely impairs activation of the small GTP-binding protein Rac and cell invasion in breast cancer cell lines and U87 in vitro. Experimental metastasis assays in nude mice show that inducible knockdown of PLC?1 strongly inhibits development of MDA-MB-231-derived lung metastasis and reverts metastasis formation. In addition, analysis of 60 breast cancer patients' tissues revealed an increase of PLC?1 expression in metastasis compared with the primary tumor in 50% of tissues analyzed. These data showa critical role of PLC?1 in the metastatic potential of cancer cells, and they further indicate that PLC?1 inhibition has a therapeutic potential in the treatment of metastasis dissemination. ©2008 American Association for Cancer Research.